Fuzzy AHP Method Utilization in Public-Private Partnership Infrastructure Research: A Review - Sunandar, Ali; Andriyanti, Fitri; Abd Karim, Saipol Bari; Zolkafli @Zulkifly, Umi Kalsum (Bulletin of Civil Engineering, 2026)
This study aims to  to review the utilization of the Fuzzy AHP method in PPP infrastructure research. A qualitative research design was adopted, employing a systematic literature review of articles indexed in Scopus and Web of Science and published between 2016 and 2025. The selected studies were examined using thematic analysis. The findings indicate that Fuzzy AHP is primarily applied in four major areas: risk assessment, partner and investment selection, sustainability and performance evaluation, and methodological development. The results also demonstrate a growing application of Fuzzy AHP in hybrid decision models that integrate complementary multi-criteria techniques and advanced fuzzy approaches. These developments reflect a methodological transition from standalone applications toward more integrated analytical frameworks. The novelty of this study lies in its comprehensive knowledge review of Fuzzy AHP applications within the PPP infrastructure domain and the development of a synthesized conceptual framework. The study contributes to the literature by clarifying research trajectories, identifying dominant thematic areas, and highlighting methodological evolution. The main limitations relate to the restricted database coverage and the specified time frame. Future research should conduct comparative studies with other decision-making methods to further examine methodological advancements in PPP research.